At Berkeley - Wiseman, Frederick; Davey, John (Frederick Wiseman - Intégrale Vol. 3: 1995-2016, 2016)
The University of California at Berkeley, the oldest and most prestigious member of a ten campus public education system, is also one of the finest research and teaching facilities in the world. The film, "At Berkeley", shows the major aspects of university life, its intellectual and social mission, its obligation to the state and to larger ideas of higher education, as well as illustrates how decisions are made and implemented by the administration in collaboration with its various constituencies. [www.zipporah.com]